Modulatory effects of R10 fraction of garlic (Allium sativum L.) on hormonal levels, T cell polarization, and fertility-related genes in mice model of polycystic ovarian syndrome - Somaye Falahatian; Raheem Haddad; Nafiseh Pakravan (BMC, 2022)
Abstract Polycystic ovary syndrome (PCOS) is an inflammatory endocrine-metabolic disorder related to reproductive system characterized by polycystic ovarian morphology, androgen excess, and chronic anovulation. Current treatments haven't been very successful in PCOS treatment and the problem still remains as a challenge. Therefore, new approaches should be applied to overcome the disease. Previous studies demonstrated immunomodulatory effects of R10 fraction of garlic in the treatment of inflammatory conditions such as cancer. Considering previous studies suggesting immunomodulatory therapy for PCOS, therapeutic effects of R10 fraction was evaluated in a mouse model of PCOS. To do so, PCOS was developed by intramuscular injection of estradiol valerate. Treatment with R10 fraction, isolated from garlic, was performed and the alterations in hormonal levels (estradiol, progesterone, and testosterone), T cell polarization markers (IFN-γ, IL-4, and IL-17), and expression of fertility-related genes (Gpx3 and Ptx3) were evaluated. The results showed that hormonal levels were elevated in PCOS model comparing to normal animals but were markedly modulated after treatment with R10 fraction. Moreover, a severe disturbance in T cell polarization with a significant reduction of fertility-related genes expression were detected in PCOS-induced ovaries. Treatment with R10 fraction also represented modulatory effects on T cell polarization by increasing IL-4 and decreasing IL-17 and IFN-γ levels. Accordingly, fertility-related genes were also modulated following treatment with R10 fraction in PCOS. Our study elucidated that R10 fraction of garlic possess immunomodulatory effects alleviating PCOS symptoms. This approach could be adjusted to give rise the optimum therapeutic results and considered as a candidate therapeutic approach for PCOS.